Peningkatan Kemampuam Mengenal Lambang Bilangan Melalui Media Pohon Angka Pada Anak Usia 4-5 Tahun Di PAUD Miftahussalam Singajaya - Jubaedah, Endah; Agnia, Gina Nur (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2024)
Based on initial observations, several problems were found in early childhood, namely that there were children who were not yet able to differentiate numbers, recognize the concept of total numbers, or order numbers. So a stimulating medium is needed to improve the ability to recognize number symbols. One media that can be developed to develop recognition of number symbols is by using number tree media. The aim of this research is to improve the ability to recognize number symbols through number trees in children aged 4-5 years at PAUD Miftahussalam Singajaya. This study uses a qualitative approach with the Class Action Research (CAR) method from Kemmis and Tagart. Observations, interviews and documentation were carried out for data collection. The research subjects in this paper are children aged 4-5 years at Paud Miftahussalam Singajaya, consisting of 7 female students and 9 male students. It can be seen that there is an increase in each lesson. there was an increase in the pre-cycle percentage resulting in a 55% increase in cycle I with an increase of 17.5% with a total percentage of 72.5% in the first cycle, then the researchers conducted research again in cycle II with an increase of 15% and the total number was 87 .5%. The implementation of recognizing number symbols using number tree media in children aged 4-5 years at Miftahussalam PAUD reached 87.5% in accordance with the indicators that researchers had targeted. Keywords: Recognizing Number Symbols, Number Trees, Early Childhood Education